2020
DOI: 10.18196/jerss.v4i2.8389
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis Effect of Islamicity Performance Index on the Financial Performance of Sharia Commercial Banks in Indonesia

Abstract: This research aims to find empirical effect evidence of Islamicity Performance Index on the financial performance of sharia commercial banks in Indonesia. The index of Islamicity Performance Index used in this research was the profit-sharing ratio, zakat performance ratio, equitable distribution ratio, directors-employees welfare ratio, Islamic income vs non-Islamic income, Islamic investment vs non-Islamic investment. This research used a quantitative approach and used secondary data in the form of sharia com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
4
0
2
Order By: Relevance
“…This finding explains that Islamic commercial bank financing through mudharabah and musyarakah contracts has not been effective in generating profit for banks. The results of thid study support previous research conducted by (Dewanata, et al 2016), Khasanah (2016), (Felani, et al 2020), Destian et al (2021), Djuwita etal. (2019, Rahmawati et al (2020), (Azhar, I.…”
Section: Discussionsupporting
confidence: 90%
“…This finding explains that Islamic commercial bank financing through mudharabah and musyarakah contracts has not been effective in generating profit for banks. The results of thid study support previous research conducted by (Dewanata, et al 2016), Khasanah (2016), (Felani, et al 2020), Destian et al (2021), Djuwita etal. (2019, Rahmawati et al (2020), (Azhar, I.…”
Section: Discussionsupporting
confidence: 90%
“…DPS will ensure that non-halal investments are not present in banking transactions. In research Felani et al (2020) and Fahmiyah (2016) found that Islamic investment vs non-Islamic investment had no significant effect on the disclosure of Islamic social reporting.…”
Section: Discussionmentioning
confidence: 95%
“…Sharia Bank JT offers different sorts of murabahah financing, such as murabahah domestic financing, murabahah vehicle financing, and other sales based exchanges concurring to sharia standards & (Felani et al, 2020). Sharia Bank JT includes a assortment of administrations both reserve funds and financing that apply sharia standards with contracts such as murabahah mutlaqah, wadiah yad dhamanah, istishna, and ijarah (Bagis et al, 2020).…”
Section: Murabahah Application At Sharia Bank Jtmentioning
confidence: 99%